Community Structure Perception Routing Mecbanism in Intermittently Connected Wireless Network - Fusheng Ji; Hongpei Zhang; Yan Zhang (Dianxin kexue)
Based on the differences of social relations between nodes,a community structure perception routing mechanism was proposed for the reason of low message delivery probability in intermittently connected wireless network.According to state information of nodes in each movement cycle,Markov models was established to show the state transition process among nodes,further,the centrality of node was obtained.Then considering about the centrality of node and exploiting the method of community label switching,network structure was checked dynamically.Finally,the central node in the community was chosen as the relay node to forward messages.Results show that the proposed method is accurate,and the performance of delivery ratio can be improved 90% approximately,optimizing the network performance greatly.